Analisis Menggunakan Peta Kendali I-MR dan Diagram Pareto pada Produksi Kayu Lapis di PT. SLJ Global Tbk, Samarinda - Lubis, Mery Christyn; Simanjuntak, Ferdyanto Abangan; Payana, Sandi Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to evaluate the quality of plywood production at PT. SLJ Global Tbk using the Statistical Quality Control (SQC) approach, specifically through the application of the I-MR control chart. The data used were collected from the production output during September 2021. The analysis was conducted using both the Individuals Chart (I-Chart) and the Moving Range Chart (MR-Chart), complemented by a Pareto analysis to identify the most dominant types of defects. The results indicate that the overall production process is within statistical control limits; however, there is a violation of Western Electric Rule 4, suggesting a potential shift in the production process. The most dominant types of defects identified are Press Mark, Delamination, and Overlapped, which together account for over 75% of all detected defects. These findings highlight the need for targeted improvements in these areas to enhance product quality. The study is limited by a short observation period and lacks a thorough investigation into the root causes of the defects. Future research is recommended over a longer period and should incorporate root cause analysis to support comprehensive quality improvement efforts.